Tendencies of pre-service primary school teacher practical training at higher educational institutions in Flanders (Belgium) - Holovatenko, Tetiana (Educological discourse, 2022)
The article dwells on the tendencies of pre-service primary school teacher training in Flanders (Belgium). This topic is of interest due to the updating of professional standards for the pre-service primary school teacher training, the orientation of the Ukrainian professional training system on the study and implementation of the best European practices of pedagogical training, as well as the successful experience of Flanders in terms of reforming the system of professional training of primary school teachers. The analysis of scholarly research confirms there are limited previous studies and the lack of a comprehensive analysis of the topic. The article aims at determining and justifying the tendencies of the practical training of primary school teachers in Flanders at three levels: organizational, content-technological, and assessment. Thus this is a qualitative Comparative Education study. The research data were obtained by analyzing the content of the curriculums and educational programs of the higher education institutions in Flanders. The data were processed using empirical methods of comparative research and methods of quantitative processing of research results. At the organizational level, the following tendencies have been identified: the tendency to organize pedagogical training according to a concurrent model, autonomy in identifying the duration of practical training by higher education institutions, diversification of the type of institutions where practical training of primary school teachers takes place. At the content-technological level, the following tendencies are identified: building programs according to the concentric principle, competency-based approach to practical training. At the assessment level, a tendency towards the implementation of formative assessment of the results of practical training is identified.